2021
DOI: 10.3390/galaxies9030067
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of Neutrino and Gamma-Ray Production from Relativistic Black-Hole Microquasar Jets

Abstract: Recently, microquasar jets have aroused the interest of many researchers focusing on the astrophysical plasma outflows and various jet ejections. In this work, we concentrate on the investigation of electromagnetic radiation and particle emissions from the jets of stellar black hole binary systems characterized by the hadronic content in their jets. Such emissions are reliably described within the context of relativistic magneto-hydrodynamics. Our model calculations are based on the Fermi acceleration mechanis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…In our previous works [7,9], we have adopted the proton-proton (p-p) interaction mechanism taking place inside the relativistic astrophysical outflows of microquasar jets. This also leads to the particle (pions, muons, neutrinos, etc.)…”
Section: Microquasar Jet Mechanisms Leading To Neutrino and Gamma-ray...mentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous works [7,9], we have adopted the proton-proton (p-p) interaction mechanism taking place inside the relativistic astrophysical outflows of microquasar jets. This also leads to the particle (pions, muons, neutrinos, etc.)…”
Section: Microquasar Jet Mechanisms Leading To Neutrino and Gamma-ray...mentioning
confidence: 99%
“…The observations of multi-wavelength and multi-particle emissions from the black-hole X-ray binaries (BHXRBs) [3][4][5] and the AGNs have shown that they are mainly due to the mass accretion onto the compact object (black hole or neutron star). The accreted matter comes from a companion (donor) star which is often a nearby main sequence star [6,7]. Thus, the inflow (from the companion star) into the accretion disc and the outflow in the jet motivate the investigation of the disc-jet connection [8] in the latter systems.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several cooling mechanisms such as syncrotron emission, collisions with the rest of the jet matter and adiabatic jet expansion tend to stall the proton energetic boosting and set an upper limit for particle energy usually of the order E max ≈ 10 7 GeV for protons and secondary particles 6,7 . In previous works, we used this model for the neutrino and gamma-ray emission prediction from extragalactic system LMC X-1 8 .…”
Section: Introductionmentioning
confidence: 99%